When will they finally see the power of drawing - Rinckhout, Erik; Geukens & De Vil Contemporary Art, Antwerpen (Antwerpen : Geukens & De Vil, 2010)
Alys, Francis ; Baelen, Steven ; Bellinkx, Ruben ; Berghe, Luk ; Bervoets, Fred ; Borremans, Michaël ; Broucke, Koen ; Buggenhout, Peter ; Claerbout, David ; Clinckx, Christine ; Cole, Stijn ; Coolen, Caroline ; Copers, Leo ; Daems, Anne ; De Beul, Bert ; De Boe, Rik ; De Bruyckere, Berlinde ; de Cordier, Thierry ; De Cupere, Peter ; De Keyser, Raoul ; De Maesschalck, Jan ; Delrue, Ronny ; Delvoye, Wim ; De Wilde, Johan ; Bois, Arpaïs du ; Eerdekens, Fred ; Fabre, Jan ; Fierens, Kris ; Geys, Jef ; Hanssen, Karin ; Heck, Kati ; Hillen, Jan ; Ivens, Renaat ; Kiefer, Gideon ; Lerooy, Thomas ; Mannaerts, Valérie ; Martin, Kris ; Meuris, Wesley ; Morrens, Peter ; Muller, Sofie ; Nicolodi, Renato ; de Beeck, Hans Op ; Panamarenko ; Raveel, Roger ; Serneels, Stefan ; Swennen, Walter ; Timmermans, Ante ; Tuymans, Luc ; Van Bossche, Guy ; Van Caeckenbergh, Patrick ; de Velde, Rinus Van ; van den Broek, Koen ; Van Imschoot, Jan ; Benoît ; Van Kerckhoven, Anne-Mie ; Van Lierop, Marilou ; Vanmechelen, Koen ; Vanriet, Jan ; Vergara Santiago, Angel ; Vermeersch, Pieter ; Wright, Cindy ; Zoete, Dirk
Catalogus n.a.v. de tentoonstelling 'When will they finally see the power of drawing' in Geukens & De Vil Contemporary Art te Antwerpen, 09.12.2010 - 22.01.2011
Nederlands
boek